A RISK FACTOR STUDY OF VISUAL ACUITY IN PTERYGIUM PATIENTS ON BAWEAN ISLAND, INDONESIA, 2023 - Handayani, Rizki Matta; Jelita, Erdina Hana; Kaptuti, Ujik Unari Dwi; Anandita, Faizal Ablansah (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesPterygium is associated with excessive exposure to sunlight and UV rays in the eyes. This causesisland countries in Asia which are in the "pterygium belt", including Indonesia, to have a highprevalence of pterygium. Other risk factors, such as gender, age, and medical conditions, such asblood pressure and diabetes, have also been linked to this chronic eye disease. However, of themany studies that have examined pterygium and its risk factors, very few have linked these riskfactors to the severity or grade of the pterygium. This study aimed to study the correlation betweenpterygium severity and its risk factors, within the people of Bawean Island, Indonesia. MethodsThis research was an analytic cross-sectional, with the research sample selected by total samplingmethod based on the results of a diagnosis performed by ophthalmologists. The research variablewere visual acuity (good-blindness), the severity / grade of pterygium (I-IV), gender, age,occupational group, pterygium location, blood pressure, and fasting blood sugar. ResultsFrom 62 patients with pterygium, 75,8% categorized as grade IV, and 41,93% has a moderate toblindness visual acuity. More than half of the patients are old female above 50 years old with 40,32%has an occupational risk of sunlight exposure. ConclusionThe results of this study indicate that although all the risk factors studied did not have a significantyon the visual acuity, age (p=0,13) and occupational groups (p=0,20) are determinant factors on thevisual acuity of pterygium patients on Bawean Island, Indonesia.